ANALISIS PROBLEM POSING SISWA DITINJAU DARI TAKSONOMI BLOOM - Saddam Hussen; Abdur Rahman Asari; Tjang Daniel Chandra (Jurnal Kajian Pembelajaran Matematika, 2017)
This study aimed to describe the analysis of problem posing students in terms of taxonomy bloom. Mathematical material that is chosen is a square and a triangle. This study used a qualitative approach with descriptive research. This study was conducted in one of the SMP Negeri Malang, with research subjects IX class consisting of 32 students. Researchers gave math tests to be analyzed based on blooms taxonomy, and researcher mengkategorisasikannya by high-level thinking skills or Higher Order Thinking Skills (HOTS) and low-level thinking skills or Lower Order Thinking Skills (LOTS). The results of this study indicate that: (1) 96.875% of the 32 students to questions categorized remembering, understanding, and applying, therefore the students included LOTS. (2) there is one category of students including analyzing, it means the student has included HOTS.